ID 317 – On the clinical value of measuring the increase in duration of the motor evoked potential with contraction-induced facilitation. Issue 3 (March 2016) - Brum, M.; Cabid, C.; Arca, R.; Banea, O.; Casanova- Molla, J.; Valls-Solé, J.
Abstract : Objective: Contraction-induced facilitation of the motor evoked potential (MEP) to transcranial magnetic stimulation (TMS) consists in three main changes: shortening of onset latency, enhancement of peak-to-peak amplitude and increase in duration. We hypothesized that the latter can be of clinical utility and retrospectively investigated how it is affected by disease. Methods: We revised data obtained in 50 patients with different neurological disorders who, as part of their clinical assessment, received focal TMS at rest and during contraction, with recording on the 1st interossesous (INT) and/or tibialis anterior (TA). We measured the MEP duration difference between facilitation and rest. Results: Healthy subjects increased the MEP duration during a mild contraction by 8.1 ± 1.1 ms in INT and by 9.8 ± 1.7 ms in TA. Patients with spastic paraparesis and a number of those with multiple sclerosis had polyphasic long duration MEPs in TA already at rest, with little increase during contraction. Patients with stroke, if they had the possibility to contract, increased duration up to normal levels. Patients with psychogenic weakness did not increase MEP duration. Conclusion: Duration of the MEP during facilitation may reveal the engagement of excitatory spinal cord premotoneuronal interneurons and may be useful for the assessment of weakness.